PERAN KEPALA SEKOLAH DALAM SUPERVISI PEMBELAJARAN GURU DI TK KRISTEN RAJAWALI SAKTI-3 PALANGKA RAYA - Natali Purwanti; Erta Marni Miranti; Yoan Colina (CV. ADIBA AISHA AMIRA, 2026)
The principal plays a crucial role in improving the quality of learning through instructional supervision activities. Instructional supervision aims to assist teachers in developing their professional and pedagogical competencies and enhancing the effectiveness of classroom learning. Based on preliminary observations at TK Kristen Rajawali Sakti-3 Palangka Raya, the principal conducted supervision through various guidance and coaching activities to support the improvement of learning quality. This study aimed to describe the principal's role in supervising teachers' instructional activities at TK Kristen Rajawali Sakti-3 Palangka Raya. This study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation involving the principal and teachers as research participants. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the principal acted as a mentor, supervisor, motivator, and evaluator in the implementation of learning activities. The principal provided guidance through meetings, classroom supervision, routine discussions, training programs, evaluations, and motivation for teachers. These roles contributed to improving learning quality, classroom management, and teacher professionalism at TK Kristen Rajawali Sakti-3 Palangka Raya.